Physicochemical Study of Ethanol Ratio in the Transesterification Process for Biodiesel Synthesis from Kesambi (Schleichera Oleosa) Seed Oil - Dani, Dani Hari tunggal Prasetiyo; Alief, Alief Muhammad; Nasrul, Nasrul Ilminnafik (International Journal of Integrated Engineering, 2024)
The demand for energy, particularly for fossil fuels, has been increasing in line with the growing number of transportation units. However, natural resource conditions such as fossil fuels are not always fulfilled. This is because fossil fuels are categorized as non-renewable resources. Moreover, all countries in the world are required to reduce the use of fossil resources and increase the use of green energy. Therefore, alternative green energy sources are needed to replace fossil fuels. Biodiesel is a green energy source that could be produced from renewable resources. Biodiesel could be obtained from non-food sources such as Kesambi oil. In this research, the biodiesel production process was carried out by esterification and transesterification methods. The transesterification process was performed by varying the molar ratio between ethanol and Kesambi oil. The molar ratio used in the transesterification process were 4:1, 6:1, 8:1, 10:1, and 12:1. The results showed that the molar ratio of 12:1 produced the lowest values of density, viscosity, and flash point, which were 0.839 g/ml, 3.98 CST, and 109.4°C, respectively, but the highest values of calorific value and yield, which were 9,040 cal/g and 91.30%, respectively